Governance for smarter KPIs - Kiron, David; Schrage, Michael; Candelon, François; Khodabandeh, Shervin; Chu, Michael (MIT Sloan Management Review, 2023)
In this final article in a series of four, the researchers behind the 2023 MIT Sloan Management Review-BCG Artificial Intelligence and Business Strategy Big Ideas research project explore how organizations should govern smart KPIs (KPIs augmented by or created with AI). They explain which functions should be involved and what pitfalls to watch for.
"November 2023.". - Includes bibliographical references
Keywords: Performance standards; Performance -- Management; Organizational effectiveness